The Use of Instagram to Improve Students’ Writing Skills in Explanation Text for Eleventh Grade Students - Kencana, Cariesa Tirta (RETAIN, 2022)
Social media has affected our daily life especially for students in this current era. Students always use social media during their life, and they can learn many things from social media. The most used social media by the students is instagram. This study takes advantage to learn from social media which is instagram especially for English subject. The point of this study is to see if using instagram may help students enhance their writing skills in Explanation Text for eleventh grade students. A quantitative research is applied by the researcher. The method utilized by the researcher was pre-experimental. The participants in this study were eleventh grade students from one of Gresik's Senior High Schools. A total of 32 students were included in the sample. Pre-test and post-test tests were employed as instruments in this study. SPSS Statistics 26 was used to perform the data analysis. The mean post-test score was (79.56), which was higher than the mean pre-test score (67.97). The t-test score was -9.991 with a degree of freedom (df) of 31 according to the data analysis. It signifies that the students' grades differed greatly. As a result, H0 is denied, but Ha is approved. Therefore, instagram is a beneficial tool for students to learn explanation text through social media. To summarize, instagram can be utilized to help students enhance their writing skills while creating explanation texts.